23+7(8n-3)=

Simple and best practice solution for 23+7(8n-3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 23+7(8n-3)= equation:


Simplifying
23 + 7(8n + -3) = 0

Reorder the terms:
23 + 7(-3 + 8n) = 0
23 + (-3 * 7 + 8n * 7) = 0
23 + (-21 + 56n) = 0

Combine like terms: 23 + -21 = 2
2 + 56n = 0

Solving
2 + 56n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 56n = 0 + -2

Combine like terms: 2 + -2 = 0
0 + 56n = 0 + -2
56n = 0 + -2

Combine like terms: 0 + -2 = -2
56n = -2

Divide each side by '56'.
n = -0.03571428571

Simplifying
n = -0.03571428571

See similar equations:

| 3.4x+48.8=19.6-11.2x | | 5x+4=-8+3x+16 | | 9(2x-8)-3=9(x-7)+6 | | 2x-8=6+4x | | 5x-2+3+x=58-2 | | 11h-14=8h-5 | | -7s=-8s-5 | | 21-9=6n | | 24x-9-16x+2=22x-7-14x+16 | | 8x-18=-30 | | -(6x-3)+6x= | | 3a+9b=30 | | 10x-10-4=3x-27x+20 | | (120+2x)(50+2x)=0 | | 10x-10-4=3x-27x+29 | | 6x+4(x-2)= | | (8x^2+5x-9)+(3x^2+8x)= | | 3(2y-3)=5(y+3) | | -8-h=8-5h | | 3(2y-3)=(y+3) | | N-0.7=3.9 | | 50-5x+5x=50 | | 160-5x=140 | | 6.50h+5=21.25 | | 9-x+35=5 | | -x-1=5x+53 | | 3x-9=21x+3 | | 3.50x=5.25-11 | | x^2-14x-250=0 | | 6+4x=2x+12 | | 71=3x-4 | | 8y+6x=40 |

Equations solver categories